Pain Reduction After Laser Acupuncture Treatment in Geriatric Patients with Knee Osteoarthritis: a Randomized Controlled Trial - Dwi R Helianthi; Christina Simadibrata; Adiningsih Srilestari; Edy R Wahyudi; Rudy Hidayat (Acta Medica Indonesiana, 2016)
Aim: to compare the effectiveness of active laser acupuncture with placebo on reducing pain intensity and improving functional outcome in geriatric patients with knee osteoarthritis (OA). Methods: a double-blind randomized controlled trial was conducted in geriatrics with knee OA at Medical Acupuncture Outpatient Clinic, Integrated Geriatric Outpatient Clinic, Rheumatology Outpatient Clinic of Cipto Mangunkusumo Hospital, Jakarta, during May to October 2015. Sixty two patients with knee OA  were randomly assigned into two groups: active laser acupuncture group or placebo laser acupuncture group. Interventions were carried out using a gallium aluminum arsenide laser device at the ST35 Dubi, ST36 Zusanli, SP9 Yinlingquan, GB34 Yanglingquan and EX - LE - 4 Neixiyan acupuncture points on the affected knee for ten sessions of treatment, i.e. twice a week. Patients were assessed using a visual analogue scale (VAS) and Lequesne index at baseline, after four sessions, after nine sessions and at 2 weeks after the treatment had been stopped. Results: the VAS scores were significantly improved in the active laser acupuncture group compared to the placebo group. The evaluation of VAS scores was carried out after four treatment sessions (mean difference: 0.39; p<0.001), after nine treatment sessions (mean difference: 37.48; p<0.001) and at 2 weeks post intervention (mean difference: 39.15; p<0.001). The evaluation also showed significant improvement of Lequesne index after four treatment sessions (mean difference: 4.68; p<0.001), after nine treatment sessions (mean difference: 5.90; p<0.001) and at 2 weeks post intervention (mean difference: 6.48; p<0.001). Conclusion: active laser acupuncture is effective in reducing pain.